Inhibition Activity of Basil Leaf Extract on The Growth of Eschericia coli, Salmonela typhi and Listeria monocytogenes - Ary Widnyani, Ida Ayu; Semadi Antara, Nyoman; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 2 No 2 (2014): September)
The research aim was to determine the inhibition activity of basil leaf extract against Eschericia coli, Salmonela typhi, and Listeria monocytogenes, and to find out the minimum inhibitory concentration (MIC) of the extract. This research used split plot design consisting with 2 factors. First factor as a mai n plot was various solvents (Et-OH, Et-ast, and hexane) and the second factor as a sub main plot was various extract concentrations (100 ppm, 200 ppm, 300 ppm, 400 ppm, and 500 ppm). Each experiment was repeated 3 times and the data were analyzed by analysis of variances, followed by Duncan’s multiple range test. The result showed that the interaction of main plot and sub plot affected significantly, the growth of E. coli, S. typhi and L. monocytogenes. The extraction process using ethanol 70% produced the best extract of basil leaf. This extract could inhibit the growth of E. coli, S. typhi and L. monocytogenes with the MIC of about 200 ppm, 100 ppm and 200 ppm respectively. The extraction process using hexane produced basil leaf extract which it only could inhibit S. typhi with MIC of about 500 ppm. Otherwise, the extraction process using Et-ast produced basil leaf extract which it could inhibit S. typhi and L. monocytogenes with the MIC of about 200 ppm for both bacteria.
Keywords: 25,